Breeding Place, Dengue Hemorrhagic Fever (DHF) at Peureulak Barat Public Health Center, East Aceh Regency, 2025 - Arianto, Budi; Aditama, Wiwit; Khairunnisa, Khairunnisa; Syima Alhumaira, Sitty Nahdatul (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2025)
The existence of breeding sites plays a significant role in increasing the population of Aedes aegypti mosquitoes, the primary vector of Dengue Fever (DHF). To determine the relationship between the type of breeding site and the incidence of DHF in the Peureulak Barat Community Health Center, East Aceh Regency, in 2025. Method: This quantitative study used a case-control design. The sample consisted of 16 cases (with DHF) and 16 controls (without DHF). Data were collected through observation and interviews and analyzed using the Chi-Square test. Results: There was no association between water reservoirs and DHF incidence (p=0.066), there was a significant association between non-water reservoirs and DHF incidence (p=0.029), and there was no association between natural water reservoirs and DHF incidence (p=0.394). Conclusion: The type of breeding site most associated with DHF incidence is non-water reservoirs. The community needs to increase their 3M Plus (National Disposal and Sanitation) activities, especially for used containers that have the potential to hold water.